Expression of haloacid dehalogenase gene and its molecular protein characterization from Klebsiella pneumoniae ITB1 - Ridani Rino Anggoro; Enny Ratnaningsih (Universitas Gadjah Mada, 2017)
Organohalogen compounds are widely used industrially and agriculturally, as well as in households as flame retardants and refrigerants. However, these compounds can become significant pollutants through their accidental or deliberate release into the environment in large quantities. Dehalogenase is an enzyme with the potential to be used in the removal of organohalogen contaminants. A previous study successfully subcloned a 690 bp of haloacid dehalogenase gene (hakp1) from Klebsiella pneumoniae ITB1 into a pET-30a(+) expression system to achieve high enzyme productivity. IPTG was used as an inducer to express a pET-hakp1 recombinant clone in Escherichia coli BL21 (DE3). The molecular mass of the haloacid dehalogenase Hakp1 protein was 30 kDa as determined by SDS-PAGE. Zymogram analysis showed that this recombinant protein has dehalogenase activity as shown by the formation of AgCl white precipitate. A quantitative assay of haloacid dehalogenase Hakp1 gave a specific activity of 84.29 U/mg with the optimum temperature of 40°C at pH 9. Predicted three-dimensional structure of Hakp1 showed α/β motif folding which comprised of cap and core domain. The predicted active sites of Hakp1 were Asp8, Glu10, Leu22, Phe23, Trp90, Ser125, Ser126, Lys159, and Asp184 with Asp8, Glu10, Ser126, and Lys159 act as binding residue. This recombinant haloacid dehalogenase clone provides an alternative agent for effective bioremediation of organohalogen pollutants.